The relationship between depression and D-deficiency in patients with type 2 diabetes mellitus under conditions of chronic stress of war - Bobryk, Maryna (Psychosomatic Medicine and General Practice, 2024)
Тези доповіді до IV Конгресу з міжнародною участю «Психосоматична медицина ХХІ століття: реалії та перспективи»